Case-Mix System as a Boundary Object: The Case of Home Care Services. Issue 3 (August 2014) - Sajtos, Laszlo; Rouse, Paul; Harrison, Julie; Parsons, Matthew
Governments worldwide face the challenges of an ageing population. New models of health services are being established to support older people to continue living in their homes with timely access to quality health services. Health care provision for older people, however, involves multiple stakeholders, who represent different views on health care, while working towards a common goal. This study presents an action-oriented collaborative process between funders, service providers and clinicians that showcases the development of a client classification (case-mix) system for home-based support service provision in New Zealand. In doing so, this study draws on the concept of boundary objects and develops a unique framework that explicitly showcases the process of aligning diverse stakeholder interests to reach a consensus. This study demonstrates how different manifestations of a single boundary concept-object can effectively bridge all knowledge boundaries and thus develops a new way of using boundary objects for creating effective collaborations.